High-nickel ternary positive electrode material as well as preparation method and application thereof
Through the combination of the three-stage program temperature-controlled calcining process and the lithium source modifier, the problem of lithium-nickel mixed discharge phenomenon in the preparation process of single crystal high-nickel ternary cathode materials is solved, and the discharge specific capacity of the material and the first-time Coulomb efficiency are improved.
Patent Information
- Application Number
- CN202311222215.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-21
Smart Images

Figure CN119695138A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a high-nickel ternary positive electrode material and a preparation method and application thereof. Background Art
[0002] Since the lithium-ion battery was first commercialized by Sony in the 1990s, the development of lithium-ion batteries with higher energy density has attracted widespread attention. High-nickel ternary cathode materials with high specific capacity, which are oriented to high energy density, have become the focus of attention. High-nickel ternary cathode materials are composed of alternating stacked lithium atomic layers and transition metal atomic layers. Since the radius of divalent nickel ions is close to that of lithium ions, lithium-nickel mixing is very likely to occur during material synthesis and electrochemical reactions, resulting in a significant decrease in the structural stability, first coulomb efficiency and charge-discharge capacity of the material.
[0003] Traditional polycrystalline high-nickel ternary positive electrode materials have a large number of grain boundaries in their structure, which are prone to side reactions with electrolytes during electrochemical reactions, and are prone to secondary ball cracking during long cycles, causing rapid attenuation of battery performance. Therefore, single-crystal high-nickel ternary positive electrode materials have also become one of the hot areas of research. Single-crystal materials have the characteristics of large primary particles and smooth particle surfaces, and their structural stability and long-term cycle stability are significantly better than polycrystalline materials. CN107910534A discloses a solid-phase preparation method for NCM811 type high-nickel ternary positive electrode materials, including raw material mixing, primary sintering in three stages, coating with composite coating agents, secondary sintering, and sintering post-treatment process steps. However, for single-crystal materials, on the one hand, single-crystal materials require higher calcination temperatures during the preparation process, which easily leads to the occurrence of lithium-nickel mixed row phenomena, which is not conducive to the performance of the material charge-discharge specific capacity and the first coulomb efficiency. On the other hand, the larger primary particle size reduces the kinetic rate of lithium ion deintercalation, which is not conducive to the performance of the material discharge specific capacity and rate performance. Summary of the invention
[0004] In view of the problems in the prior art that the single crystal positive electrode material has a high degree of lithium-nickel mixing and a large particle size resulting in poor electrochemical performance, the present invention provides a high-nickel ternary positive electrode material and a preparation method and application thereof. The positive electrode material of the present invention can greatly improve the discharge specific capacity and first coulombic efficiency of lithium batteries.
[0005] The present invention first provides a high nickel ternary positive electrode material, the chemical formula of which is Li x Ni y Co z M a N b O c, M is at least one of Mn and Al, N is at least one of Ti, V, Nb, Zr, Ta, W or Mo, preferably at least one of Nb, W, Ti or Mo; 0.9≤x<1.2, 0.6≤y≤0.95, 0<z≤0.2, 0<a≤0.2, 0<b≤0.02, and the values of x, y, z, a, b, and c conform to the principle of electrical neutrality; the positive electrode material has a single crystal morphology, an average size of primary particles is 0.20-1.50 microns, and a c / a ratio in the lattice parameters is greater than 4.9360.
[0006] In the above technical solution, the positive electrode material has a single crystal morphology, and the average size of the primary particles is 0.20-0.95 microns, preferably 0.30-0.90 microns.
[0007] In the above technical solution, in the positive electrode material, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.15, 0<a≤0.15; preferably, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.05, 0<a≤0.15.
[0008] In the above technical solution, in the positive electrode material, the c / a ratio in the lattice parameter is greater than 4.9370.
[0009] In the above technical solution, in the XRD refinement result of the positive electrode material, the lithium-nickel mixing degree is greater than 3% and less than 10%. Preferably, the lithium-nickel mixing degree is greater than 3% and less than 6%.
[0010] A second aspect of the present invention provides a method for preparing a high-nickel ternary positive electrode material, comprising:
[0011] A high-nickel ternary positive electrode material precursor, a lithium source and a modifier are mixed, calcined and crushed to obtain the positive electrode material.
[0012] In the above technical solution, the lithium source is one or more of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium phosphate or lithium oxalate, preferably at least one of anhydrous lithium hydroxide or lithium hydroxide monohydrate.
[0013] In the above technical solution, the high nickel ternary positive electrode material precursor is a hydroxide precursor containing nickel-cobalt-manganese, nickel-cobalt-aluminum or nickel-cobalt-manganese-aluminum, and its chemical formula is Ni y Co z M a (OH) 2, wherein M is at least one of Mn and Al; 0.6≤y≤0.95, 0<z≤0.2, 0<a≤0.2, and y+z+a=1; preferably, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.15, 0<a≤0.15, and y+z+a=1; further preferably, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.05, 0<a≤0.15, and y+z+a=1.
[0014] In the above technical solution, the modifier is TiO 2 、V 2 O 5 , Nb 2 O 5 、ZrO 2 、 2 O 5 , WO 3 or MoO 3 One or more, preferably TiO 2 , Nb 2 O 5 , WO 3 or MoO 3 One or more of.
[0015] In the above technical solution, the molar ratio of the lithium source to the high-nickel ternary positive electrode material precursor is 1:1 to 1.3:1, preferably 1.05:1 to 1.2:1.
[0016] In the above technical solution, the molar ratio of the modifier to the high-nickel ternary positive electrode material precursor is 0.002:1 to 0.02:1, preferably 0.005:1 to 0.01:1.
[0017] In the above technical solution, the calcination is carried out by three-stage programmed temperature control calcination, wherein the temperature T 1 The calcination time is 400-600℃ and t 1 The second stage calcination temperature is 4-7 hours. 2 800-1100℃, calcination time t 2 The third stage calcination temperature is 0.1-6 hours. 3 600-900℃, calcination time t 3 6-18 hours.
[0018] In the above technical solution, during the first stage calcination, the temperature is raised from room temperature (25-30°C) to T at a rate of 2-8°C / min. 1 Preferably, the temperature of the first stage calcination is T 1 450-550℃, time t 1 For 5-7 hours.
[0019] In the above technical solution, during the second stage calcination, from T 1 The temperature was raised to T at a rate of 2-10°C / min. 2 Preferably, the temperature of the second stage calcination is T 2 850-1000℃, time t 2 0.5-4 hours.
[0020] In the above technical solution, during the third stage calcination process, from T 2 Cool down to T at a rate of 2-10℃ / min 3 Preferably, the temperature of the third stage calcination is T 3 700-800℃, time t 3 9-15 hours.
[0021] In the above technical solution, during the three-stage programmed temperature control calcination process, t 2 Less than t 1 and t 3 , and T 2 Greater than T 1 and T 3 Preferably, the calcination temperature and time follow t 3 >t 1 >t 2 , and T 2 >T 3 >T 1 The law of.
[0022] In the above technical solution, during the three-stage calcination process, the calcination atmosphere is one of nitrogen, air or high-purity oxygen. Preferably, the calcination atmosphere is one of air or high-purity oxygen.
[0023] In the above technical solution, the mixing adopts a conventional physical mixing method to make the ternary positive electrode material precursor fully contact with the lithium source, such as grinding.
[0024] In the above technical solution, the crushing method is air flow crushing or ball mill crushing, and the crushing time is 2-10 hours, preferably 4-8 hours.
[0025] In the above technical solution, the high nickel ternary positive electrode material has a chemical formula of Li x Ni y Co z M a N b O c, M is at least one of Mn and Al, N is at least one of Ti, V, Nb, Zr, Ta, W or Mo, preferably at least one of Nb, W, Ti or Mo; 0.9 ≤ x < 1.2, 0.6 ≤ y ≤ 0.95, 0 < z ≤ 0.2, 0 < a ≤ 0.2, 0 < b ≤ 0.02, and the values of x, y, z, a, b, c conform to the principle of electrical neutrality.
[0026] In the above technical solution, in the positive electrode material, 0.9 ≤ x < 1.1, 0.8 ≤ y ≤ 0.95, 0 < z ≤ 0.15, 0 < a ≤ 0.15; preferably, 0.9 ≤ x < 1.1, 0.8 ≤ y ≤ 0.95, 0 < z ≤ 0.05, 0 < a ≤ 0.15.
[0027] In the above technical solution, the positive electrode material has a single crystal morphology, and the average size of the primary particles is 0.20 - 1.50 μm, preferably 0.20 - 0.95 μm, and more preferably 0.30 - 0.90 μm.
[0028] In the above technical solution, in the positive electrode material, the c / a ratio in the lattice parameter is greater than 4.936, preferably, the c / a ratio is greater than 4.937.
[0029] In the above technical solution, in the XRD refinement result of the positive electrode material, the lithium-nickel mixing degree is greater than 3% and less than 10%, preferably, the lithium-nickel mixing degree is greater than 3% and less than 6%.
[0030] The third aspect of the present invention provides the application of the high-nickel ternary positive electrode material as described above in a lithium-ion battery.
[0031] Furthermore, the application includes: mixing, coating, and slicing the above positive electrode material with a conductive agent and a binder for use as a battery positive electrode. The conductive agent and the binder can be various conductive agents and binders conventionally used in the art. For example, the conductive agent can be selected from at least one of acetylene black, Ketjen black, graphite, carbon nanotubes, and graphene. The binder can be selected from at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), and sodium carboxymethyl cellulose (CMC). The amounts of the conductive agent and the binder can also be conventional amounts in the art. For example, the mass ratio of the positive electrode material: conductive agent: binder is 0.8 - 0.96: 0.1 - 0.02: 0.1 - 0.02.
[0032] Furthermore, the lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. There are no particular limitations on the negative electrode, the separator, and the electrolyte, and those skilled in the art can reasonably select them without having to make creative efforts. For the sake of comparison, in the embodiments of the present invention, metallic lithium is used as the negative electrode, a 16 μm polyethylene microporous membrane of Jinhui Hi-Tech is used as the separator, and 1 mol / L LiPF 6The solution is a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7.
[0033] Furthermore, the battery is assembled in an inert atmosphere glove box, and the moisture and oxygen content in the glove box is less than 0.1 ppm. There is no particular limitation on the battery model. For year-on-year comparison, 2016 button batteries are generally used in the embodiments of the present invention. The electrochemical performance is tested on a blue battery test system at an electrochemical test temperature of 30°C.
[0034] The method of preparing lithium batteries using positive electrode materials is well known in the art and will not be described here.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The present invention provides a high-nickel ternary positive electrode material having a single crystal morphology, a small primary particle size, a moderate lithium-nickel mixing degree, and a large c / a ratio in the lattice parameters obtained by XRD results, indicating that the prepared ternary material has good crystallinity and layered structure, and can effectively improve the discharge specific capacity and first coulombic efficiency of the single crystal positive electrode material.
[0037] (2) The high-nickel ternary cathode material of the present invention is prepared by introducing ion modification in a three-stage programmed temperature rise calcination process. At the same time, due to the introduction of modified elements into the system, although the lithium-nickel mixing degree is increased to a certain extent, the primary particle size is relatively reduced, shortening the transmission path of lithium ions during the charge and discharge process, effectively improving the lithium ion deintercalation kinetics rate, thereby improving the discharge specific capacity and first coulomb efficiency of the single crystal cathode material. Specifically, by regulating the parameters such as the calcination time and calcination temperature in the temperature rise program, the lithium salt and the precursor hydroxide are promoted to melt and react initially in the first stage calcination process, and in the second stage calcination process, the highest T 2 The temperature ensures the formation of single crystal morphology of positive electrode material, and at the same time, the shortest t 2 The time ensures the lowest energy consumption for material preparation. In the third calcination process, the moderate T 3 Temperature and longer t 3 Under the premise of ensuring that the degree of lithium-nickel mixing in the material is not too high, the modified ions further promote the refinement of the primary particles in the bulk phase of the positive electrode material.
[0038] (3) The new single-crystal ternary positive electrode material prepared by the present invention exhibits higher discharge specific capacity and first coulombic efficiency when applied to button-type lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a SEM image of the high-nickel ternary positive electrode material prepared in Example 1 of the present invention;
[0040] Figure 2 0.1C charge and discharge curve of the battery in Example 1 of the present invention;
[0041] Figure 3 This is a SEM image of the high-nickel ternary positive electrode material prepared in Comparative Example 1 of the present invention;
[0042] Figure 4 This is the 0.1C charge and discharge curve of the battery in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0043] For ease of understanding of the present invention, the present invention enumerates embodiment as follows. But those skilled in the art should understand that the embodiment is only to help understand the present invention, should not be regarded as specific limitation of the present invention. The endpoints and any value of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values.
[0044] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.
[0045] In the context of this specification, any two or more aspects of the present invention may be arbitrarily combined, and the technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0046] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.
[0047] In the present invention, the scanning electron microscope (SEM) images were obtained by using a Nova Nano 450 field emission scanning electron microscope.
[0048] In the present invention, the XRD pattern is measured by using a D8 ADVANCE model x-ray diffractometer.
[0049] In the present invention, the obtained XRD spectrum is refined by using Topas software and Rietveld full spectrum fitting refinement method. When the reliability factor Rwp of the refined sample is less than or equal to 5%, the lithium-nickel mixing degree of the sample can be obtained.
[0050] In the present invention, the average size of the primary particles is measured by using Nano measurer particle size analysis software on a scanning electron microscope image, and the average value of the data in the measurement results with sizes in the 10%-90% percentile is calculated.
[0051] The present invention will be described in detail below through examples.
[0052] [Example 1]
[0053] (1) Preparation and evaluation of ternary cathode materials
[0054] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and 0.15 g Nb 2 O 5 Powder and mix well and grind;
[0055] The homogeneous powder obtained above was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere. The temperature was increased from 30°C to 500°C at a heating rate of 5°C / min, and maintained for 7 hours. The temperature was then increased to 900°C at a heating rate of 10°C / min, and maintained for 4 hours. The temperature was then decreased to 700°C at a cooling rate of 5°C / min, and maintained for 12 hours. The temperature was then naturally decreased to below 100°C and taken out.
[0056] The powder obtained after high-temperature calcination is ball-milled for 4 hours to obtain a high-nickel ternary positive electrode material.
[0057] Figure 1 This is a SEM image of the high-nickel ternary positive electrode material obtained in Example 1. As can be seen from the figure, the obtained high-nickel ternary positive electrode material mainly presents a single crystal morphology, and the average size of the primary particles is 0.90 μm.
[0058] (2) Electrochemical properties of cathode materials
[0059] The positive electrode material was mixed with conductive carbon and binder PVDF in a ratio of 0.9:0.05:0.05 in NMP and then coated on aluminum foil, dried, sliced, and assembled into a 2016-type button battery in a glove box.
[0060] Figure 2 The charge and discharge curve of the battery assembled with the above positive electrode material at a rate of 0.1C is shown in the figure. As can be seen from the figure, the discharge capacity of the obtained battery at a rate of 0.1C is 189.8mAh / g, and the first coulombic efficiency is 86.17%.
[0061] [Example 2]
[0062] (1) Preparation and evaluation of ternary cathode materials
[0063] Take 10g of high nickel ternary cathode material precursor Ni0.83 Co 0.05 Mn 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and 0.25 g Ta 2 O 5 Powder and mix well and grind;
[0064] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere at a heating rate of 5°C / min from 30°C to 500°C, maintained for 7h, then heated to 900°C at a heating rate of 10°C / min, maintained for 4h, then cooled to 700°C at a cooling rate of 5°C / min, maintained for 12h, and then naturally cooled to below 100°C and taken out;
[0065] The powder obtained after high-temperature calcination is ball-milled for 4 hours to obtain a high-nickel ternary positive electrode material.
[0066] SEM image of the high nickel ternary positive electrode material obtained in Example 2 Figure 1 Similarly, the average size of the primary particles was 0.80 μm.
[0067] (2) Electrochemical properties of cathode materials
[0068] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0069] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0070] [Example 3]
[0071] (1) Preparation and evaluation of ternary cathode materials
[0072] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and 0.08 g TiO 2 Powder and mix well and grind;
[0073] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere. The temperature was increased from 25°C to 550°C at a heating rate of 5°C / min, maintained for 7 hours, then increased to 900°C at a heating rate of 10°C / min, maintained for 3 hours, then cooled to 750°C at a cooling rate of 5°C / min, maintained for 12 hours, and then naturally cooled to below 100°C and taken out;
[0074] The powder obtained after high-temperature calcination is ball-milled for 4 hours to obtain a high-nickel ternary positive electrode material.
[0075] SEM image of high nickel ternary positive electrode material obtained in Example 3 Figure 1 Similarly, the average size of the primary particles was 0.83 μm.
[0076] (2) Electrochemical properties of cathode materials
[0077] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0078] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0079] [Example 4]
[0080] (1) Preparation and evaluation of ternary cathode materials
[0081] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 , add 5g LiOH·H 2 O powder and 0.15 g Nb 2 O 5 Powder and mix well and grind;
[0082] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere. The heating rate was 5°C / min, from 25°C to 500°C, maintained for 7h, then heated to 900°C at a heating rate of 10°C / min, maintained for 4h, then cooled to 700°C at a cooling rate of 5°C / min, maintained for 12h, and then naturally cooled to below 100°C and taken out.
[0083] The powder obtained after high-temperature calcination is ball-milled for 4 hours to obtain a high-nickel ternary positive electrode material.
[0084] SEM image of high nickel ternary positive electrode material obtained in Example 4 Figure 1 Similarly, the average size of the primary particles was 0.86 μm.
[0085] (2) Electrochemical properties of cathode materials
[0086] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0087] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0088] [Example 5]
[0089] (1) Preparation and evaluation of ternary cathode materials
[0090] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and 0.27 g WO 3 Powder and mix well and grind;
[0091] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere at a heating rate of 5°C / min from 30°C to 500°C, maintained for 7h, then heated to 900°C at a heating rate of 10°C / min, maintained for 2h, then cooled to 700°C at a cooling rate of 5°C / min, maintained for 15h, and then naturally cooled to below 100°C and taken out;
[0092] The powder obtained after high-temperature calcination is ball-milled for 8 hours to obtain a high-nickel ternary positive electrode material.
[0093] SEM image of the high nickel ternary positive electrode material obtained in Example 5 Figure 1 Similarly, the average size of the primary particles was 0.62 μm.
[0094] (2) Electrochemical properties of cathode materials
[0095] The lithium battery was assembled according to the method described in Example 5, and the electrochemical performance was tested.
[0096] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0097] [Example 6]
[0098] (1) Preparation and evaluation of ternary cathode materials
[0099] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and 0.18 g MoO 3 Powder and mix well and grind;
[0100] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere at a heating rate of 5°C / min from 30°C to 500°C, maintained for 7h, then heated to 900°C at a heating rate of 10°C / min, maintained for 1h, then cooled to 700°C at a cooling rate of 5°C / min, maintained for 12h, and then naturally cooled to below 100°C and taken out;
[0101] The powder obtained after high-temperature calcination is ball-milled for 8 hours to obtain a high-nickel ternary positive electrode material.
[0102] SEM image of the high nickel ternary positive electrode material obtained in Example 6 Figure 1 Similarly, the average size of the primary particles was 0.38 μm.
[0103] (2) Electrochemical properties of cathode materials
[0104] The lithium battery was assembled according to the method described in Example 6 and the electrochemical performance was tested.
[0105] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0106] [Example 7]
[0107] (1) Preparation and evaluation of ternary cathode materials
[0108] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Al 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and 0.08 g TiO 2 Powder and mix well and grind;
[0109] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere. The temperature was increased from 25°C to 550°C at a heating rate of 5°C / min, maintained for 7 hours, then increased to 900°C at a heating rate of 10°C / min, maintained for 3 hours, then cooled to 750°C at a cooling rate of 5°C / min, maintained for 12 hours, and then naturally cooled to below 100°C and taken out;
[0110] The powder obtained after high-temperature calcination is ball-milled for 4 hours to obtain a high-nickel ternary positive electrode material.
[0111] SEM and Figure 1 Similarly, the average size of the primary particles was 0.76 μm.
[0112] (2) Electrochemical properties of cathode materials
[0113] Assemble the lithium battery according to the method described in Example 7 and test the electrochemical performance.
[0114] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0115] [Comparative Example 1]
[0116] (1) Preparation and evaluation of ternary cathode materials
[0117] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and 0.05g MgO powder and mix and grind thoroughly;
[0118] The homogeneous powder obtained above was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere. The temperature was increased from 30°C to 500°C at a heating rate of 5°C / min, and maintained for 7 hours. The temperature was then increased to 900°C at a heating rate of 10°C / min, and maintained for 4 hours. The temperature was then decreased to 700°C at a cooling rate of 5°C / min, and maintained for 12 hours. The temperature was then naturally decreased to below 100°C and taken out.
[0119] The powder obtained after high-temperature calcination is ball-milled for 4 hours to obtain a high-nickel ternary positive electrode material.
[0120] Figure 3 This is the SEM image of Comparative Example 1. As can be seen from the figure, the obtained high-nickel ternary positive electrode material mainly presents a single crystal morphology, and the average size of the primary particles is 3.40 μm.
[0121] (2) Electrochemical properties of cathode materials
[0122] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0123] Figure 4 The charge and discharge curve of the battery at a rate of 0.1C. As can be seen from the figure, the discharge capacity of the obtained battery at a rate of 0.1C is 145.2mAh / g, and the first coulombic efficiency is 74.59%.
[0124] [Comparative Example 2]
[0125] (1) Preparation and evaluation of ternary cathode materials
[0126] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2, add 5g LiOH·H 2 O particles and 0.15 g Nb 2 O 5 Powder and mix well and grind;
[0127] The homogeneous powder obtained above was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere at a heating rate of 5°C / min from 30°C to 550°C, maintained for 7h, then heated to 930°C at a heating rate of 10°C / min, maintained for 12h, and naturally cooled to below 100°C before being taken out;
[0128] The powder obtained after high-temperature calcination is ball-milled for 4 hours to obtain a high-nickel ternary positive electrode material.
[0129] SEM image of high nickel ternary positive electrode material obtained in Comparative Example 2 Figure 1 Similarly, the average size of the primary particles was 2.50 μm.
[0130] (2) Electrochemical properties of cathode materials
[0131] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0132] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0133] [Comparative Example 3]
[0134] (1) Preparation and evaluation of ternary cathode materials
[0135] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and 0.15 g Nb 2 O 5 Powder and mix well and grind;
[0136] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere. The specific process was as follows: the temperature was increased from 30°C to 500°C at a heating rate of 5°C / min, maintained for 7h, then increased to 700°C at a heating rate of 10°C / min, maintained for 4h, then increased to 900°C at a heating rate of 10°C / min, maintained for 12h, and then naturally cooled to below 100°C and taken out;
[0137] The powder obtained after high-temperature calcination was ball-milled for 4 hours to obtain the ternary positive electrode material.
[0138] SEM images of the ternary cathode material obtained in Comparative Example 3 and Figure 1 Similarly, the average size of the primary particles was 2.10 μm.
[0139] (2) Electrochemical properties of cathode materials
[0140] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0141] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0142] [Comparative Example 4]
[0143] (1) Preparation and evaluation of ternary cathode materials
[0144] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and 0.15 g Nb 2 O 5 Powder and mix well and grind;
[0145] The obtained homogeneous powder was subjected to high temperature treatment in a tube furnace and calcined in an oxygen atmosphere. The specific process was as follows: the temperature was increased from 30°C to 700°C at a heating rate of 5°C / min, maintained for 7 hours, then increased to 1000°C at a heating rate of 10°C / min, maintained for 4 hours, then cooled to 500°C at a cooling rate of 10°C / min, maintained for 12 hours, and then naturally cooled to below 100°C and taken out;
[0146] The powder obtained after high-temperature calcination was ball-milled for 4 hours to obtain the ternary positive electrode material.
[0147] The SEM image of the ternary positive electrode material obtained in Comparative Example 4 is Figure 1 Similarly, the average size of the primary particles was 2.80 μm.
[0148] (2) Electrochemical properties of cathode materials
[0149] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0150] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0151] [Comparative Example 5]
[0152] (1) Preparation and evaluation of ternary cathode materials
[0153] Take 10g of high nickel ternary cathode material precursor Ni 0.83 Co 0.05 Mn 0.12 (OH) 2 , add 5g LiOH·H 2 O powder and mix and grind thoroughly;
[0154] The homogeneous powder obtained above was subjected to high temperature treatment in a tube furnace and sintered in an oxygen atmosphere. The temperature was increased from 30°C to 500°C at a heating rate of 5°C / min, and maintained for 7 hours. The temperature was then increased to 900°C at a heating rate of 10°C / min, and maintained for 4 hours. The temperature was then decreased to 700°C at a cooling rate of 5°C / min, and maintained for 12 hours. The temperature was then naturally decreased to below 100°C and taken out.
[0155] The powder obtained after high-temperature calcination is ball-milled for 4 hours to obtain a high-nickel ternary positive electrode material.
[0156] SEM image of high nickel ternary positive electrode material obtained in comparative example 5 Figure 1 Similarly, the average size of the primary particles was 3.00 μm.
[0157] (2) Electrochemical properties of cathode materials
[0158] Lithium batteries were assembled according to the method described in Example 1 and the electrochemical performance was tested.
[0159] The electrochemical performance at a rate of 0.1C was measured, and the specific results are shown in Table 2.
[0160] Table 1 Physicochemical properties of high nickel ternary positive electrode materials obtained in each example
[0161] sample Chemical formula of positive electrode material c / a Lithium-nickel mixing degree Example 1 <![CDATA[Li[Ni 0.83 Co 0.05 Mr 0.12 ] 0.99 No 0.01 O 2 ]]> 4.9379 4.831% Example 2 <![CDATA[Li[Ni 0.83 Co 0.05 Mr 0.12 ] 0.99 Dad 0.01 O 2 ]]> 4.9361 6.938% Example 3 <![CDATA[Li[Ni 0.83 What 0.05 Mn 0.12 ] 0.99 Those 0.01 O 2 ]]> 4.9387 5.045% Example 4 <![CDATA[Li[Ni 0.83 Co 0.12 Mr 0.05 ] 0.99 No 0.01 O 2 ]]> 4.9363 6.872% Example 5 <![CDATA[Li[Ni 0.83 What 0.12 Mn 0.05 ] 0.985 IN 0.015 ABOUT 2 ]]> 4.9382 5.117% Example 6 <![CDATA[Li[Ni 0.83 Co 0.12 Mr 0.05 ] 0.985 Mo 0.015 O 2 ]]> 4.9378 4.735% Example 7 <![CDATA[Li[Ni 0.83 Co 0.05 Al 0.12 ] 0.99 Of 0.01 SHE 2 ]]> 4.9383 4.982% Comparative Example 1 <![CDATA[Li[Ni 0.83 Co 0.05 Mr 0.12 ] 0.99 Mg 0.01 O 2 ]]> 4.9352 6.203% Comparative Example 2 <![CDATA[Li[Ni 0.83 Co 0.05 Mr 0.12 ] 0.99 No 0.01 O 2 ]]> 4.9279 12.968% Comparative Example 3 <![CDATA[Li[Ni 0.83 Co 0.05 Mr 0.12 ] 0.99 No 0.01 O 2 ]]> 4.9334 8.476% Comparative Example 4 <![CDATA[Li[Ni 0.83 Co 0.05 Mr 0.12 ] 0.99 No 0.01 O 2 ]]> 4.9261 10.042% Comparative Example 5 <![CDATA[LiNi 0.83 What 0.05 Mn 0.12 ABOUT 2 ]]> 4.9387 1.722%
[0162] Table 2 Electrochemical performance test results of high nickel ternary positive electrode materials obtained in each example
[0163]
[0164]
[0165] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A high-nickel ternary cathode material with the chemical formula Li x Ni y Co z M a N b O c , where M is at least one of Mn and Al, N is at least one of Ti, V, Nb, Zr, Ta, W, or Mo, preferably at least one of Nb, W, Ti, or Mo; 0.9 ≤ x < 1.2, 0.6 ≤ y ≤ 0.95, 0 < z ≤ 0.2, 0 < a ≤ 0.2, 0 < b ≤ 0.02, and the values of x, y, z, a, b, and c conform to the principle of electroneutrality; the cathode material has a single-crystal morphology, the average size of the primary particles is 0.20 - 1.50 microns, and the c / a ratio in the lattice parameters is greater than 4.9360.
2. The high-nickel ternary positive electrode material according to claim 1, characterized in that: In the positive electrode material, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.15, 0<a≤0.15; preferably, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.05, 0<a≤0.
15.
3. The high-nickel ternary positive electrode material according to claim 1, characterized in that: The average size of the primary particles is 0.20-0.95 micrometers, preferably 0.30-0.90 micrometers.
4. The high-nickel ternary positive electrode material according to claim 1, characterized in that: In the positive electrode material, the c / a ratio in the lattice parameter is greater than 4.9370.
5. The high-nickel ternary positive electrode material according to claim 1, characterized in that: In the XRD refinement result of the positive electrode material, the lithium-nickel mixing degree is greater than 3% and less than 10%. Preferably, the lithium-nickel mixing degree is greater than 3% and less than 6%.
6. A method for preparing a high-nickel ternary positive electrode material, comprising the following steps: A high-nickel ternary positive electrode material precursor, a lithium source and a modifier are mixed, calcined and crushed to obtain the positive electrode material.
7. The preparation method according to claim 6, characterized in that: The calcination adopts three-stage programmed temperature control calcination, wherein the temperature T1 of the first stage calcination is 400-600°C, the calcination time t1 is 4-7 hours, the temperature T2 of the second stage calcination is 800-1100°C, the calcination time t2 is 0.1-6 hours, and the temperature T3 of the third stage calcination is 600-900°C, and the calcination time t3 is 6-18 hours.
8. The preparation method according to claim 6, characterized in that: The temperature T1 of the first stage calcination is 450-550°C, the time t1 is 5-7 hours, and the heating rate is 2-8°C / min; the temperature T2 of the second stage calcination is 850-1000°C, the time t2 is 0.5-4 hours, and the heating rate is 2-10°C / min; the temperature T3 of the third stage calcination is 700-800°C, the time t3 is 9-15 hours, and the heating rate is 2-10°C / min.
9. The preparation method according to claim 7 or 8, characterized in that: t2 is smaller than t1 and t3, and T2 is larger than T1 and T3; preferably, the calcination temperature and time follow the rule of t3>t1>t2, and T2>T3>T1.
10. The preparation method according to claim 6, characterized in that: The lithium source is one or more of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium phosphate or lithium oxalate, preferably one or more of anhydrous lithium hydroxide or lithium hydroxide monohydrate; And / or, the modifier is one or more of TiO2, V2O5, Nb2O5, ZrO2, Ta2O5, WO3 or MoO3, preferably one or more of TiO2, Nb2O5, WO3 or MoO3.
11. The preparation method according to claim 6, characterized in that: The high-nickel ternary positive electrode material precursor is a hydroxide precursor containing nickel-cobalt-manganese, nickel-cobalt-aluminum or nickel-cobalt-manganese-aluminum, and its chemical formula is Ni y Co z M a (OH)2, wherein M is at least one of Mn and Al; 0.6≤y≤0.95, 0<z≤0.2, 0<a≤0.2, and y+z+a=1; preferably, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.15, 0<a≤0.15, and y+z+a=1; further preferably, 0.9≤x<1.1, 0.8≤y≤0.95, 0<z≤0.05, 0<a≤0.15, and y+z+a=1.
12. The preparation method according to claim 6, characterized in that: The molar ratio of the lithium source to the ternary cathode material precursor is 1:1 to 1.3:1, preferably 1.05:1 to 1.2:1; and / or, the molar ratio of the modifier to the high-nickel ternary cathode material precursor is 0.002:1 to 0.02:1, preferably 0.005:1 to 0.01:1; And / or, the crushing method is air flow crushing or ball mill crushing, and the crushing time is 2-10 hours, preferably 4-8 hours.
13. The preparation method according to claim 6, characterized in that: The chemical formula of the positive electrode material is Li x Ni y Co z M a N b O c , where M is at least one of Mn and Al, N is at least one of Ti, V, Nb, Zr, Ta, W, or Mo, preferably at least one of Nb, W, Ti, or Mo; 0.9 ≤ x < 1.2, 0.6 ≤ y ≤ 0.95, 0 < z ≤ 0.2, 0 < a ≤ 0.2, 0 < b ≤ 0.02, and the values of x, y, z, a, and b satisfy the principle of electroneutrality.
14. A high-nickel ternary positive electrode material prepared by the method according to any one of claims 6 to 13.
15. Use of the high-nickel ternary positive electrode material according to any one of claims 1 to 5 or the high-nickel ternary positive electrode material according to claim 14 in a lithium-ion battery.
Citation Information
Patent Citations
Preparation method of high-nickel ternary material
CN108346797A
High-nickel single-crystal nickel-cobalt-aluminum ternary positive electrode material and preparation method thereof
CN113422046A
Positive electrode active material with superlattice structure, preparation method and lithium ion battery
CN113611849A
Spherical-like single crystal positive electrode material and preparation method thereof
CN114481322A
Method for preparing high-capacity single-crystal ternary positive electrode material by infiltration dispersion method
CN114703545A
Cited By
Doping and coating integrated modified high-nickel ternary positive electrode material as well as preparation method and application thereof
CN120581559A
Positive electrode material and preparation method thereof, positive electrode plate, secondary battery and electric device
CN121215736A
Positive electrode material and preparation method thereof, positive plate and lithium ion battery
CN121726402A
A positive electrode material, a preparation method thereof, a positive electrode sheet, and a lithium ion battery
CN121726402B